Peran Sistem Informasi Manajemen Dalam Meningkatkan Efisiensi Rumah Sakit - Lisa Maharani; Aisah, Siti (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2024)
The study aims to ascertain how the implementation of the Hospital Management Information System (SIMRS) affects the efficiency of health care. Accurate and quick information from management information systems significantly simplifies decision-making and problem-solving processes of the company. Information systems enable hospitals to continue to have good planning, control, and functional capabilities. The research uses a riview literature study approach that focuses on an approach using several selected sources using databases such as Google Scholar. The results of this research show that innovations in the development of information systems based on business process management, automation of service flows, cost reduction, improved hospital performance, aimed at human resource development, organizational development, and technology quality to enhance efficiency of hospital services can reduce the complexity of health care.